DEVELOPMENT STRATEGIES FOR RURAL TOURISM IN DOBROGEA - Daniela-Mirela PLEȘOIANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Rural tourism has a number of advantages and is characterized by diversity in time and space, and has recently become an essential element of rural development policy. Its practice allows for visible and clearly measurable results, and they contribute to the economic development of the area. The purpose of this paper is to highlight the importance of rural tourism in Dobrogea, tourism that has major implications in the local and national economy, by:generating economic benefits for local communities, organizations and authorities dealing with natural areas, with a view to preserving them; providing new jobs and additional sources of income for local communities; raising awareness - both by locals and tourists - of the preservation of natural and cultural assets. Dobrogea rural areas have a very valuable tourism potential, being valued by imposing development strategies, such as: developing and modernizing tourist infrastructure, preserving and protecting natural areas, existing historical and religious potential, developing and modernizing all bases touristic; development and modernization of accommodation services, making the most of the anthropic tourism; increasing the quality of the services provided and the qualification of the staff involved in tourism activities; attracting tourists through an extensive program of advertising and carrying out projects that highlight the elements of the cultural, historical and typical rural heritage.